SYNTAX OF THE TIV RELATIVE CLAUSE - Ishima, Jighjigh Leo-Justus; Ikwu, Lucy Oyidu; Idoko, Theresa Dora (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
The study interrogates the syntax of relative clauses and explores issues dominant in its analysis. Issues interrogated include restrictive and non-restrictive analysis; mediated and unmediated analysis under the canopy of principles and parameters approach (Chomsky, 2001), seeking to know how the relative clause in the Tiv language is accounted for, under the frame of those dominant forms of analyses. The methodology employed for the study involved interrogating the various strategies which the Tiv language adopts in the selection and structuring of those specific features that become characteristic of the language and form its parameters. The data obtained for the study sought to answer questions that discern the relation between the relative head and the relativized site. The analysis tried to see whether or not the head of the relative clause plays a dual role such as being part of the matrix clause, serving syntactic and semantic function in RC internal position, and whether the RC is a complement, or an adjunct of the DP. The findings of the study show that Tiv exhibits overt relative markers. Also, the RPr is the central component that serves the link between the other elements in the construction, inferring that the relation is an indirect one, mediated by the RPr, thus agreeing with the concept of mediated analysis. The findings also agree with the assumption of the RC being the complement of the determiner derived by movement of the head noun into the SPEC position of the relative CP, and also that there is long distance binding. Data treatment shows that Tiv favours both mediated and unmediated analysis in its treatment of relative clauses.